Human papillomavirus type 7‐associated anal condyloma after renal transplantation in a child. (12th May 2019) - Garaix, Florentine; Hery, Geraldine; Tsimaratos, Michel; Colson, Philippe; Tamalet, Catherine
Abstract: The prevalence, clinical significance, and spectrum of many HPV genotypes are currently largely untapped. We report a case of anal condyloma associated with a rare HPV genotype in a 11‐year‐old kidney transplant recipient. Eleven months post‐graft, rectal bleeding revealed a 5‐cm‐large anal condyloma for which immuno‐histopathology revealed typical papillomatosis. HPV genotyping performed on anal biopsy identified a HPV type 7, for which a single sequence was found in the GenBank sequence database. HPV7 is classically found in hand cutaneous warts, but HPV7‐associated condyloma was only described in two patients. Total resection of the anal lesion was performed by electrocoagulation with no recurrence after 6 years. Post‐transplant immunosuppression may promote anal condyloma with uncommon HPV types. HPV genotyping in such lesions is useful to get a better understanding of the epidemiology and clinical significance of such unusual HPV types as HPV7.